2016
DOI: 10.1021/acs.biochem.5b00774
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Activation of cGMP-Dependent Protein Kinase by a Nitrated Cyclic Nucleotide via Site Specific Protein S-Guanylation

Abstract: 8-Nitroguanosine 3',5'-cyclic monophosphate (8-nitro-cGMP) is a nitrated derivative of guanosine 3',5'-cyclic monophosphate (cGMP) formed endogenously under conditions associated with production of both reactive oxygen species and nitric oxide. It acts as an electrophilic second messenger in the regulation of cellular signaling by inducing a post-translational modification of redox-sensitive protein thiols via covalent adduction of cGMP moieties to protein thiols (protein S-guanylation). Here, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…4,5) We previously determined the lipophilicity of 8-nitro-cGMP and 8-bromocGMP on the basis of octanol/water partition coefficient measurements, and we found 8-nitro-cGMP to be less lipophilic than 8-bromo-cGMP. 12) Consistent with this result, we found that tissue levels of Rp-8-nitro-cGMPS were lower than those of Rp-8-bromo-cGMPS after mouse aortic rings were incubated with those inhibitors (Fig. 7).…”
Section: )supporting
confidence: 84%
See 4 more Smart Citations
“…4,5) We previously determined the lipophilicity of 8-nitro-cGMP and 8-bromocGMP on the basis of octanol/water partition coefficient measurements, and we found 8-nitro-cGMP to be less lipophilic than 8-bromo-cGMP. 12) Consistent with this result, we found that tissue levels of Rp-8-nitro-cGMPS were lower than those of Rp-8-bromo-cGMPS after mouse aortic rings were incubated with those inhibitors (Fig. 7).…”
Section: )supporting
confidence: 84%
“…12) In brief, 1 µg/mL PKG1α (total 10 ng) was incubated with Rp-8-bromo-cGMP or Rp-8-nitro-cGMP at concentrations of 1, 10, or 100 µM for 90 min before the kinase experiments. PKG1α reaction mixtures with inhibitors were then used as kinase mixes during incubation with cGMP at different concentrations (0, 1, 10, or 100 µM) in 20 mM TrisHCl (pH 7.4) containing 16 mM MgCl 2 , 10 mM dithiothreitol, 0.1 mM ATP, and 60 µM Glasstide (Merck Millipore) at 37°C for 30 min.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations